Analysis of Welding Procedure Specifications for steel line pipe material - Rudi Suhradi Rachmat; Lydia Anggraini; Wandesmoni Sihotang; Kei Ameyama (SINERGI, 2022)
This study proposes the welding process steel line pipe material of API5L Grade X52 diameter Ø8 inch SCH80 type, subjected to the good quality of the product by following the Welding Procedure Specifications (WPS). The purpose of welding using WPS is to ensure that the welding process follows the correct stages because the steps are proper. The weld results will be free from defects and safe for line pipes. In order to confirm the WPS quality, the characterisations of macrostructure, microstructure, and mechanical properties were analysed. The welding process results by following the procedure specifications, from macrostructure shown no porosity, and sample without following the welding procedure specifications shown porosity at weld metal position. The tensile test sample following the welding procedure specifications showed high strength and ductility compared with the samples without welding procedure specifications. This phenomenon occurs due to the grain size of the martensitic structure and a little bit of growth compared with a sample without following the welding procedure specifications. Furthermore, the bending test result shows that both samples have no crack at the weld metal position.